Effects of organic manures on yield and yield attributes of coffee (Coffea arabica L.) genotypes - Chaudhary, Jeet Narayan; Bhusal, Yuba Raj; Gotame, Tek Prasad; Thapa, Krishna Bahadur; Shrestha, Deepa Singh; Shrestha , Jiban (Journal of Agriculture and Natural Resources, 2022)
An experiment was carried out to determine the effects of organic sources of fertilizers on yield and yield parameters of five coffee (Coffea arabica) genotypes at Gulmi district in 2015 to 2021. Five different source of organic manures (mustard cake @ 2 kg/plant, poultry manure @ 2.5 kg/plant, vermi compost @ 3 kg/plant, goat manure @ 4 kg/plant and FYM/cattle manure @ 5 kg/plant) was applied on five coffee genotypes (Chhetradip Local, Gulmi Local, Selection-10, Syangja Special and Yellow Cattura). Field experiment was laid out in factorial randomized complete block design with three replications. Irrespective of genotypes, the length of cherry was found maximum (15.3 mm) in mustard cake applied plants which was followed by poultry manure applied plants (15.2 mm). The average cherry length was found longest (15.3 mm) in Yellow Cattura and Syangja Special which was followed by genotype Chhetradip Local (15.1 mm). The highest diameter of cherry (12.7 mm) was obtained with the use of mustard cake followed by poultry manure (12.4 mm). The application of mustard cake produced the highest cherry yield (3.55 kg/plant) followed by poultry manure (3.43 kg/plant). Yellow Cattura produced the highest fresh cherry yield (3.34 kg/ha) followed by Selection-10 (3.07 kg/plant). Results indicate that poultry manure and Yellow Cattura are most effective for higher production of coffee.